Inclusion in sport: disability and participation - Kiuppis, Florian (Sport in society, 2018)
For the last couple of decades UNESCO has aimed to achieve to a far extent the implementation of the guiding principle of inclusion at all levels in education systems worldwide. The idea that countries 'should ensure an inclusive education system at all levels' is also a central objective of the UN Convention on the Rights of Persons with Disabilities. This Introduction to the Special Issue explores what participation as an aspect of inclusion means in general, and realistically can mean in sport and quality physical education in particular. Sport is introduced as a context in which, unlike in education, the individual choice of a sporting activity on a spectrum ranging from separate activities for persons with disabilities to modified activities designed for all makes it necessary to attribute each approach equal importance and validity instead of discrediting segregated structures and glorifying supposedly inclusive ones.